Reception of Città Ideale: Italian Renaissance cultural impact upon town planning in Poland - Motak, Maciej (International Planning History Society Proceedings, 2018)
The concept of the Ideal City, as developed in Italy during the 15th and 16th centuries, has produced a significant number of treatises with texts and drawings, which, largely speaking, are theoretical rather than applied. Although new Renaissance towns were quite a rare phenomenon both in Italy and in other countries, a number of such towns were constructed in the Polish-Lithuanian Commonwealth. Two types of new towns were built according to their basic functions: the town-and-residence compounds were prestigious family seats combined with adjacent towns, while the “economic” towns were local trading centres. The fashionable ideas and forms of the Città Ideale were adopted by those towns’ founders and planners. Selected examples of Polish Renaissance towns are discussed in this paper. Apart from Zamosc (1578, designed by Bernardo Morando and often considered the most perfect Ideal City, and not only in Poland), other slightly less ideal though equally interesting townand- residence compounds are also described: Zolkiew (1584, now Zhovkva, Ukraine) and Stanislawow (1662, now Ivano-Frankivsk, Ukraine). Three of the “economic” towns are also presented here: Glowow (1570, now Glogow Malopolski), Rawicz (1638) and Frampol (founded as late as c. 1717, although still of a purely Renaissance form).